Evaluation of Poultry Shop Business Compensation System Based On Job Value Using Hay Job Evaluation Methods - Adinda Yom; Rindi Anti Nur Fadilah; Shafira putri; Sitria Maulida (Ridwan Institute, 2021)
Compensation is one of the crucial things in a company that needs to be designed accordance with the 3Ps (Pay for person, pay for performance, and pay for position) so that employees can give their best contribution to the company. In this case, it is necessary to determine the grading between positions that reflects the knowledge, skills, and responsibilities of employees at each level. One of the weighting criteria can used are based on the Hay System, which is classified based on know- how, problem solving, and accountability. Budi Poultry Shop is one of the SMEs in Magelang which is engaged in chicken farming in partnership with PT Malindo Feedmill Tbk. The purpose of this study is to evaluate the payroll system in the Budi Poultry Shop compensation to be more fair and effective for each employee based on Job Value & Job Grading using hay job evaluation methods and a salary mapping system with the Adhered method and the Overlapping method. The data used in this study are primary data and secondary data obtained through the distribution of questionnaires, interviews, and literature studies to various sources relevant to the research. Based on the results of data processing, it is found that the compensation system for the SME Budi Poultry Shop is less than ideal. The ideal compensation system is to use an analysis of the salary mapping compensation system with the overlapping method to implement the efficiency of funds issued by SMEs